Sambandha as a ‘Śakti-of-Śaktis’: Bhartṛhari’s Influence on the Relational Realism of Pratyabhijñā - Berger, Jesse (Religions, 2023)
Contemporary scholarship has significantly advanced our understanding of the grammarian Bhartṛhari’s influence on the Pratyabhijñā Śaivism of Utpaladeva and Abhinavagupta. One area that has been somewhat neglected, however, is the subject of relation (sambandha). Here, I examine the influence of Bhartṛhari’s sambandha-vāda on the Pratyabhijñā school. As I see it, Bhartṛhari’s understanding of the holistic movement of sphoṭa—the practical process of ‘encoding’ and ‘decoding’ linguistic information—leads to a necessary reevaluation of the general logical form of sambandha, i.e., ‘relationality-as-such.’ On this account, Bhartṛhari articulates a basically transcendental conception of sambandha as a ‘śakti-of-śaktis’ in his ‘Exposition of Relation’ (Sambandhasamuddeśa [SSam]). This effectively means that one cannot designate the general logical form of sambandha in linguistic terms without also thereby changing its essential nature as such (cf. Houben: 170–4). I maintain that Utpaladeva’s ‘Proof of Relation’ (Sambandhasiddhi [SS]) leverages this insight into a series of pragmatic arguments to demonstrate that vimarśa, or recognitive judgment, is the true locus of relational action—i.e., unity-in-diversity (bhedābheda). In doing so, he effectively salvages a coherent understanding of relation as necessarily real (satya) from the deconstructive agenda of the Buddhist eliminativist, even though the referent may indeed appear paradoxical from the perspective of theoretical reason alone.